IBM z/OS V2R2 storage management and utilities - Winnard, Keith (IBM redbooks, 2015)
This IBM® Redbooks® publication helps you to become familiar with the technical changes that were introduced into the Storage Management and Utilities areas with IBM z/OS V2R2. This book is one of a series of IBM Redbooks that take a modular approach to providing information about the updates that are included with z/OS V2R2. This approach has the following goals: - Provide modular content - Group the technical changes into a topic - Provide a more streamlined way of finding relevant information that is based on the topic We hope you find this approach useful and we welcome your feedback.